I. Studies toward the total synthesis of triptoquinone A and triptinin A. II. Conjugate addition of sulfonyl carbanions to chiral α,β-unsaturated oxazolines - Basil, Laura F., author; Meyer, A. I., advisor (Colorado State University. Libraries, 2001)
I. The synthesis of the natural products triptoquinone A and triptinin A was approached by a strategy that involved a tandem addition to a chiral 3,4-dihydronaphthyl oxazoline. The tandem addition of a vinyl lithium and a homoallylic iodo-electrophile was successful and highly stereoselective. The synthesis of the requisite oxazoline and the electrophile was developed. The tandem-addition product then underwent a ring-closing metathesis to close the C-ring thereby putting in place the triptinin/triptquinone ring system and carbon backbone. Transformation of the oxazoline moiety into a quaternary methyl group was studied, as was the removal of an allylic alcohol protecting group. II. Several examples of conjugate addition of sulfonyl carbanions to acyclic, chiral α,β-unsaturated oxazolines were shown to occur with very high stereoselectivity and good yield. In the examples where cyclization followed addition, three contiguous stereocenters were set in one reaction step. It was noted that the pKa's of both the sulfonyl nucleophile and the oxazolinyl acceptor should be matched appropriately in order for the reaction to be efficient.
Studies toward the total synthesis of triptoquinone A and triptinin A
Conjugate addition of sulfonyl carbanions to chiral α,β-unsaturated oxazolines
Keywords: organic chemistry